Giysi kirlilik algısı: Kullanıcı deneyimleri üzerine bir araştırma - ÖZBEK, AHMET (My University, 2023)
Clothes are undoubtedly one of the most polluting products in our world due to the pollution they create both during production and during washing after use. Because of this importance, the main purpose of this research is to determine in which situations clothing users perceive the clothing as dirty. For this purpose, a questionnaire has designed. Data have obtained from 337 people through the related questionnaire. From the analysis of the obtained data; It has been concluded that women’s perception of pollution is higher than men’s, and that clothing pollution perception differs according to age and education level, but not according to income levels. In addition, in terms of the perception of the contamination time of the clothes; It has been determined that there is a significant difference according to gender, age, education level and income variable. In addition, the majority of users perceive the garment as dirty if there is an odor in the garment, the garment is contaminated with sweat, and the garment is worn for long periods of travel. In addition, users; They perceive the clothes worn for less than half a day in hot weather, two days in cold weather, and three days or more in the house as dirty.

Giysiler hem üretilirken hem de kullanım sonrası yıkanma sırasında oluşturdukları kirlilik nedeniyle kuşkusuz dünyamızı en çok kirleten ürünlerin başında gelmektedir. Bu öneminden dolayı bu araştırmanın temel amacı, giysi kullanıcılarının hangi durumlarda giysiyi kirli olarak algıladıklarını belirlemektir. Bu amaçla bir anket tasarlanmıştır. İlgili anket vasıtasıyla 337 kişiden veri elde edilmiştir. Yapılan analizlerden elde edilen bulgulara göre kadınların kirlilik algısının erkeklerden daha yüksek olduğu, giysi kirlilik algısının yaşa, eğitim düzeyine göre farklılaşırken gelir düzeylerine göre farklılaşmadığı sonucuna varılmıştır. Ayrıca giysilerin kirlenme süresi algısı açısından cinsiyet, yaş, eğitim düzeyi, gelir değişkenlerine göre anlamlı bir şekilde farklılaştığı tespit edilmiştir. Ek olarak, giyside koku olması, giysiye ter bulaşması ve giysinin uzun süreli seyahatte giyilmesi durumunda kullanıcıların çoğunluğu giysiyi kirli olarak algılamaktadır. Ayrıca kullanıcılar; sıcak havada yarım günden daha az, soğuk havada iki gün ve ev içerisinde üç gün ve daha fazla giyilen giysiyi kirli olarak algılamaktadırlar.
Dirtiness perception of clothes: a research on user experiences
Keywords: Tekstil Mühendisliği ve Teknolojisi; Tekstil İşletmeciliği ve Yönetimi; Mühendislik ve Teknoloji; Textile Engineering and Technology; Textile Management; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Malzeme Bilimi; MALZEME BİLİMİ, TEKSTİL; Engineering, Computing & Technology (ENG); MATERIALS SCIENCE; MATERIALS SCIENCE, TEXTILES; Giysi Kullanımı; Kirlilik Algısı; Kullanıcı Deneyimi.; Clothing Use; Dirtiness Perception; User Experience